Analisis Struktur Aktiva, Kepemilikan Manajerial, dan Variabilitas Pendapatan Pada Struktur Modal Perusahaan Manufaktur - Pina Lestari, Ni Komang; Putu Wirawati, Ni Gusti (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p10, 2021)
The purpose of this study was to determine the effect of asset structure, managerial ownership, and income variability on the company's capital structure (DER). This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017- 2019 period. The population in this study were 181 companies, using the purposive sampling method the research sample was obtained as many as 46 manufacturing companies. The data analysis technique used in this research is panel data regression analysis technique with Eviews version 11 as a tool. Based on the research results, it is found that the asset structure has no effect on the capital structure. Managerial ownership has a positive and significant effect on capital structure. Income variability has a negative and significant effect on capital structure. Keywords:   Asset Structure; Managerial Ownership; Income  Variability; Capital Structure.